2022
DOI: 10.3390/app12094537
|View full text |Cite
|
Sign up to set email alerts
|

Ajwa-Dates (Phoenix dactylifera)-Mediated Synthesis of Silver Nanoparticles and Their Anti-Bacterial, Anti-Biofilm, and Cytotoxic Potential

Abstract: Green nanotechnology is the evolution of cost-effective and environmentally friendly processes for the production of metal-based nanoparticles due to medicinal importance and economic value. The aim of the present study was to biosynthesize and characterize silver nanoparticles (AgNPs) using the seed extract of Ajwa dates (Aw). The anti-bacteriostatic activity of biosynthesized Aw–AgNPs against Gram-positive and Gram-negative bacterial strains was evaluated. The anti-biofilm activity was examined by the tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Phoenix dactylifera L. includes phenolic acids, carotene, polyphenols, anthocyanins, and tannins, among other phytochemicals. Another investigation on the phenolic content of Ajwa dates reported the existence of three significant phenols in pharmacology: catechin, caffeic acid, and rutin [ 84 , 85 , 86 , 87 ]. Therefore, the anticancer activities reported might be attributed to the incidence of flavonoids and phenolics in dates, which are high in phenolic compounds [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phoenix dactylifera L. includes phenolic acids, carotene, polyphenols, anthocyanins, and tannins, among other phytochemicals. Another investigation on the phenolic content of Ajwa dates reported the existence of three significant phenols in pharmacology: catechin, caffeic acid, and rutin [ 84 , 85 , 86 , 87 ]. Therefore, the anticancer activities reported might be attributed to the incidence of flavonoids and phenolics in dates, which are high in phenolic compounds [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the antimicrobial results, Ag-C-1 and Ag-C-3 were selected to investigate their antibiofilm potential against E. coli and C. albicans in a polystyrene 96-well microtiter tissue culture plate, as method described by Allemailem et al [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Green synthesized Ag and ZnO NPs are the most explored nanomaterials studied for the prevention of bacterial growth and the production of biofilms. It has been reported that AgNPs synthesized by green methods using different parts of plant extracts significantly inhibit the growth of E. coli, P. aeruginosa, S. aurous, B. cereus, and K. pneumonia, and also inhibit biofilm formation [203][204][205]. In another study, it was found that biologically synthesized ZnO NPs enhanced the antimicrobial activity and inhibited the biofilm formation by E. coli and S. aureus [206,207].…”
Section: Cdse/zns Quantum Dots Dairy Product α-Lactalbuminmentioning
confidence: 97%